Aspectos epidemiológicos e fatores do parasita associados à leishmaniose visceral canina e humana - Tuñón, Gabriel Isaías Lee (2013)
Visceral leishmaniasis or kala-azar is a zoonotic disease of domestic and wild canids, caused by the protozoan Leishmania chagasi and transmitted between dogs and man by the vector Lutzomyia longipalpis. The purpose of this research was to analize the spatial distribution of human and canine cases of visceral leishmaniasis in Aracaju, Sergipe from 2005 to 2012; characterize a nitric oxide resistant and susceptible isolates of L. chagasi from dogs in Aracaju, performing proteomic analysis of it by bidimensional electrophoresis and checking their interaction between dog and fox macrophages. In the analysis of the spatial distribution of the disease during the study period, there were 2060 canine and 110 human cases. It was found that the neighborhoods, Zona de Expansão and Mosqueiro, peripheral areas with lower population densities, recent occupation, poor urban infrastructure, had a number of significant human and canine cases. In Dezoito do Forte, Santos Dumont and America neighborhoods, were isolated nitric oxide resistant Leishmania in dogs and in humans, which could confirm the dog as a source of infection for humans and maybe could confirmation that disease in dogs precedes the occurrence of the disease in humans. Infection of fox macrophages by strains of L. chagasi, revealed that the macrophages control the infection rapidly regardless of whether the strain is resistant or not to nitric oxide. This result corroborates the fact that wild canids such as foxes, have an important role in the sylvatic cycle of visceral leishmaniasis, serving as a reservoir for the disease and rarely displaying clinical forms of the disease, unlike the domestic dog. Proteomic analysis was performed in promastigotes in logarithmic and stationary phase showing a difference in the expression of many proteins in both the promastigote growth phases. As an interesting fact we observed an over-expression of a cytosolic malate dehydrogenase and that it may probably be related to an intrinsic resistance of this isolate to nitric oxide. Related to resistance to nitric oxide, overexpression of trypanothione peroxidase was constant at all stages of the growth curve. Also observed was the overexpression of a calpain that may be responsible for inducing greater susceptibility to antimonials and lower susceptibility to miltefosine.